RELEVANSI HASIAT MINYAK ZAITUN DENGAN SAINS MODERN - Muhammad Sofwan; Khusni Mubarok, Sultoni, Fatichatus Sa'diyah (CV. Adiba Aisha Amira, 2025)
The purpose of this scientific work is to find out the efficacy of Olive oil which will be solved by modern science in knowing what is meant by a text of the hadiths and the text of the Quran. This research method uses photographic or qualitative methods focused onlibrary research, which aims to collect information data with the help of various kinds of materials contained in the library such as books, journals, articles, and theses, as well as the method of takhri>j and sarah hadith. The results of this scientific work show that the hadith describing olive oil can be found in Sunan al- Tirmidhi>, Sunan ibn Ma>jah and Musnad ad-Da>rimi>. by using the book al-Mu'jam al-Mufahras li al-Fa>z al-Hadi>th al-Nabawi>, authored by Arnold John Wensick . And the direction of the hadith that shows the efficacy and benefits contained in the olive oil itself, the compiler concludes that in olive oil is a liquid that has a lot of characteristics, because this liquid can relieve or cure various diseases that sometimes in the medical world alone cannot cure contemporaneously, so medical science refers to the substance of the content of this olive oil. and this indicates that herbal medicine is an herbal treatment. and this indicates that the herbal medicine recommended by the Prophet Muhammad is proven and able to become the mecca of medical science that is developing in this day and age. olive oil, which is stated in the Qur'an and hadith, as well as a correlation that can be accounted for with the latest science.",